Stakeholders use A4NH evidence from program evaluations to inform decisions that guide and support nutrition-sensitive programming in Bangladesh - CGIAR Research Program on Agriculture for Nutrition and Health (2017)
Numerous stakeholders – donors, investors, UN agencies, and government ministries – used findings from an IFPRI-led pilot study, the Transfer Modality Research Initiative (TMRI) on integrating across sectors and the role of nutrition behavior change communication (BCC) - to inform the design of nutrition, poverty alleviation, and social protection programs and plans in Bangladesh.